Tribological performance of palm kernel oil at various load using pin-on-disk tribotester / A.M.S. Zuan... [et al.] - A.M.S., Zuan; S., Syahrullail; M.D., Arif; S., Kamitani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Vegetables oil are known as an oil resources that is renewable, non-toxic and biodegradable compared to the petroleum oil. This properties brings the researcher to study on vegetable oil as a substitute resources for an application such as lubricants. In this study, the tribological properties of Palm Kernel Oil was studied by evaluating the wear and friction characteristics of aluminium (A1100) pin lubricated with different types of oils and tested using pin on disc machine in compliance with the ASTM G99 standard. The two oils used are Palm Kernel Oil and commercial semi-synthetic engine oil. The material for spherical ended pin is aluminium A1100 while material for steel disc is SKD-11. For each test, load are varied at 1 kg, 3 kg and 5 kg. The duration of each test located is 1 hour and the linear speed of the rotating disc are kept constant at 1.5 m/s. A fixed amount of 2.5 ml of lubricant is applied to the disc. From the analysis, the coefficient of friction obtained by palm kernel oil is better than semi-synthetic engine oil. However, the value of wear scar resulted from palm kernel oil is larger than semi-synthetic engine oil. Additional additives are needed to improve the wear scar of pin lubricated by Palm Kernel Oil in the future.